'HE SAW WHAT HE WANTED TO SEE': REPUTATION, JEALOUSY, AND THE LAW. THE UXORICIDE OF GISELDA ZANOLO. (October 2021) - Delmedico, Sara
Abstract : Drawing on articles published in the Corriere della Sera, Il Popolo d'Italia and La Stampa, this study examines a case of uxoricide that occurred in 1923, focusing on the way in which the murderer and his lawyers were able to convince both the general public and the jury that the murderer's jealous nature was a mental illness, leading to him avoiding a prison sentence. The victim, the murderer's wife, was depicted as a physically attractive woman of dubious sexual reputation. Such characteristics were deemed to have triggered her husband's jealousy, thus rendering her culpable, the agent of her own homicide. In place of a picture of uxoricide in revenge for tarnished honour, the murderer portrayed himself as the powerless victim of love and jealousy. Through a close analysis of the strategy adopted by the defendant's lawyers, this article shows how centuries-old gendered stereotypes and ideas of respectability affected the law in action and permeated early twentieth-century Italian society.